Aplikasi Hallotem Platform Konsultasi Dan Layanan Pengaduan Teknisi Elektro Medis Berbasis Mobile - Syahrun Mubarok; Linda Fujiyanti; M. Syafrizal Zain (Politeknik Manufaktur Negeri Bangka Belitung, 2026)
The advancement of information and communication technology has driven digital transformation across various sectors, including healthcare. RSUD Dr. Ir. H. Ibnu Saleh, MM, in Bangka Belitung faces challenges in managing medical equipment due to a limited number of technicians and a manual reporting system for equipment malfunctions. This leads to delays in repairs and impacts the quality of healthcare services. This study aims to design and develop the HalloTEM mobile application using the Prototipe method to address these issues. The application enables real-time reporting of medical equipment malfunctions, direct consultation with technicians, and efficient management of complaint data by administrators. Developed using the Flutter framework and supported by Laravel and MySQL technologies, the application offers features such as real-time notifications via WhatsApp or in-app, complaint status tracking, and periodic reporting. The results demonstrate that HalloTEM significantly improves efficiency, accuracy, and documentation in the medical equipment repair process, thereby enhancing the overall quality of healthcare services in the hospital.